TRANSFORMATION OF THE ELECTORAL SYSTEM IN THE REPUBLIC OF KAZAKHSTAN - Nurpeisov Еркеш Калиевич; Auanasova Алима Мусировна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
The article is devoted to the evolution of the electoral system of the Republic of Kazakhstan. The authors on the basis of the analysis of the normative-legal base of the electoral system show its evolutionary way as a political instrument capable to promote both democratic development of society and its stagnation and degradation. A new turn in the development of the electoral system of Kazakhstan was conditioned by the adoption of the Constitution of the Republic of Kazakhstan dated 30 August 1995. From that time on, fundamentally new pages of the electoral system of Kazakhstan began, which chose the path of a presidential republic with a bicameral Parliament and a developed system of local representative bodies - maslikhats. Constitutional reforms from 1998 to 2017 had a significant impact on the evolution of electoral legislation of Kazakhstan in the post-Soviet period, expressed in the fact that a number of its provisions were more politically motivated than dictated by the need for further democratisation of public life and compliance with legal logic. Therefore, in order to eliminate these shortcomings of the electoral system, amendments and additions were made to the legislation provided for by the Constitutional Act of 5 November 2022. It introduced 174 amendments and additions, including 34 new articles, to the Constitutional Law on Elections of 28 September 1995. They concerned all aspects of electoral law and the practice of its application. Thus, the electoral system of Kazakhstan was brought in line with the amendments and additions to the Constitution of the Republic of Kazakhstan adopted at the republican referendum on 5 June 2022. The article is set out in a problem-chronological plan, similar or closely related events that took place in different periods of the evolution of electoral legislation, in violation of chronology, but in accordance with their logic, are set out in one place.